Continental‐scale hotspots of pelagic fish abundance inferred from commercial catch records. Issue 10 (24th August 2017) - Bouchet, Phil J.; Meeuwig, Jessica J.; Huang, Zhi; Letessier, Tom B.; Nichol, Scott L.; Caley, M. Julian; Watson, Reg A.
Abstract: Aim: Protected areas have become pivotal to the modern conservation planning toolbox, but a limited understanding of marine macroecology is hampering their efficient design and implementation in pelagic environments. We explored the respective contributions of environmental factors and human impacts in capturing the distribution of an assemblage of commercially valuable, large‐bodied, open‐water predators (tunas, marlins and mackerels). Location: Western Australia. Time period: 1997–2006. Major taxa studied: Pelagic fishes. Methods: We compiled 10 years of commercial fishing records from the Sea Around Us Project and derived relative abundance indices from standardized catch rates while accounting for confounding effects of effort, year and gear type. We used these indices to map pelagic hotspots over a 0.5°‐resolution grid and built random forests to estimate the importance of 33 geophysical, oceanographic and anthropogenic predictors in explaining their locations. We additionally examined the spatial congruence between these hotspots and an extensive network of marine reserves and determined whether patterns of co‐occurrence deviated from random expectations using null model simulations. Results: First, we identified several pelagic hotspots off the coast of Western Australia. Second, geomorphometrics explained up to 50% of the variance in relative abundance of pelagic fishes, and submarine canyon presence ranked as the most influential variable in the North bioregion. Seafloor complexity, geodiversity, salinity, temperature variability, primary production, ocean energy, current regimes and human impacts were also identified as important predictors. Third, spatial overlap between hotspots and marine reserves was limited, with most high‐abundance areas primarily found in zones where anthropogenic activities are subject to few regulations. Main conclusions: This study reveals geomorphometrics as valuable indicators of the distribution of mobile fish species and highlights the relevance of harnessing static topography as a key element in any blueprint for ocean zoning and spatial management.